Globalization and employment: imported skill biased technological change in developing countries - Andrea Conte; Marco Vivarelli (Institute for the Study of Labor (IZA), 2007)
This paper discusses the occurrence of Skill-Enhancing Technology Import (SETI), namely the relationship between imports of embodied technology and widening skill-based employment differentials in a sample of low and middle income countries (LMICs). In doing so, this paper provides a direct measure of technology transfer at the sector level from high income countries (HICs), namely those economies which have already experienced the occurrence of skill-biased technological change, to LMICs. GMM techniques are applied to an original panel dataset comprising 28 manufacturing sectors for 23 countries over a decade. Econometric results provide robust evidence of the determinants of widening employment differentials in LMICs. In particular, capital-skill complementarity represents a source of relative skill-bias while SETI provides an absolute skill-bias effect on the employment trends of skilled and unskilled workers witnessed in these countries.
urn:nbn:de:101:1-20080401334
Keywords: 330; Technologietransfer; Qualifikation; Technischer Fortschritt; Komplementärgut; Kapital; Sektorale Beschäftigungsstruktur; Globalisierung; Schwellenländer; Low-Income Countries